2019
DOI: 10.1177/1470785318822270
|View full text |Cite
|
Sign up to set email alerts
|

An integrative typology of relational benefits and costs in social media brand pages

Abstract: This article focuses on consumer–brand relationships in the social media environment and suggests a typology of the benefits and costs consumers perceive when interacting with social media brand pages. Employing an online questionnaire, quantitative data were collected from 881 followers of popular brand pages on both Facebook and Twitter. Study results indicate that followers of brand pages on Facebook and Twitter perceive “social,” “functional,” “enjoyment,” “special treatment,” “self-enhancement,” “advice,”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
2
18
0
1
Order By: Relevance
“…The quantitative survey method dominates SMAR research, adopted by over 65% (n 5 60) of the articles identified. Including mixed-method studies, seven take qualitative approaches, such as focus group interview, in-depth interview, and semantic analysis (Deraz, 2019;Kongsagoonwong and Ngamkroeckjoti, 2018;Mattke et al, 2018a;Riedel et al, 2018; Note(s): One study published in 2020 is not included Truong and Simmons, 2010;Tsimonis et al, 2020;Youn and Kim, 2019a). Additionally, seven articles involve more than one study (Ahn et al, 2017;Belanche et al, 2017;Celebi, 2015;Hamby and Ilyuk, 2019;Huang, 2019;Park et al, 2016;Tsimonis et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative survey method dominates SMAR research, adopted by over 65% (n 5 60) of the articles identified. Including mixed-method studies, seven take qualitative approaches, such as focus group interview, in-depth interview, and semantic analysis (Deraz, 2019;Kongsagoonwong and Ngamkroeckjoti, 2018;Mattke et al, 2018a;Riedel et al, 2018; Note(s): One study published in 2020 is not included Truong and Simmons, 2010;Tsimonis et al, 2020;Youn and Kim, 2019a). Additionally, seven articles involve more than one study (Ahn et al, 2017;Belanche et al, 2017;Celebi, 2015;Hamby and Ilyuk, 2019;Huang, 2019;Park et al, 2016;Tsimonis et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The emergence of social media has not only considerably changed the ways individuals interact but also altered the digital marketing landscape. Social media has become a new communication paradigm for company-to-consumer message delivery and attracted a great deal of advertising investment (Tsimonis et al, 2020). Taking the United States as an example, the total advertising budget for social media reached 32 billion US dollars in 2019, with a growth rate of 19.4% (eMarketer, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the revolution and disruptiveness that social media has become known for, there are common risks associated with influencer marketing (Tsimonis et al, 2020)…”
Section: Influencer Marketing and The Risks Around Scandalsmentioning
confidence: 99%
“…When a brand partners with well-known personalities, the brand is in essence associating that person’s public persona with the values and reputation of their brand’s intrinsic along with the reputation that the brand has worked so hard to build up (Tsimonis et al, 2020). Negative press around a partner can put an organization’s brand at risk for being “guilty by association,” leaving the organization’s brand vulnerable to any criticism that the influencer may face.…”
Section: Introductionmentioning
confidence: 99%